Implementation of Business and Human Rights Principles (UNGPs) in the Protection given to Indonesian Laborers: Gender Perspective - Arsyi Manggali Arya Putra; Nur Putri Hidayah (Jurnal Cita Hukum, 2023)
Abstract This research aims to analysis to what extent business and Human Rights principles have been implemented to protect workers/laborers in Indonesia according to the gender perspective. This research employed a normative method by analyzing the norms set forth in international law synchronized with the provisions in the statute (statutory approach) in Indonesia in a descriptive form and a conceptual approach. The research concludes that business and Human Rights principles were initiated by Ruggie as a new concept regarding corporate responsibility to meet the development of human rights. The protection of human rights for workers/laborers, especially women, has not been sufficiently given. The management of the dimension of human rights in employment-related matters requires business relations and human rights with the concept of three pillars. First, the state is responsible to prevent violations of human rights. Second, corporates are responsible to respect human rights. Third, this pillar is to manage access to the recovery of the victims of human rights violations. Furthermore, the protection of workers/laborers is governed in Employment Law that needs to be elaborated further by normalizing business and human rights principles in employment sector.